Diffusion effects in myelin sheath free induction decay - Kurz, Felix T.; Buschle, Lukas R.; Hahn, Artur; Jende, Johann; Bendszus, Martin; Heiland, Sabine; Ziener, Christian H. (Journal of magnetic resonance, 2018)
Myelin sheath microstructure and composition produce MR signal decay characteristics that can be used to evaluate status and outcome of demyelinating disease. We extend a recently proposed model of neuronal magnetic susceptibility, that accounts for both the structural and inherent anisotropy of the myelin sheath, by including the whole dynamic range of diffusion effects. The respective Bloch-Torrey equation for local spin dephasing is solved with a uniformly convergent perturbation expansion method, and the resulting magnetization decay is validated with a numerical solution based on a finite difference method. We show that a variation of diffusion strengths can lead to substantially different MR signal decay curves. Our results may be used to adjust or control simulations for water diffusion in neuronal structures.